ACM SIGGRAPH 2010 Posters 2010
DOI: 10.1145/1836845.1836897
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive games as therapy for children with FAS

Abstract: Therapies that help restore abilities in individuals with brain damage are being investigated to help individuals with FAS. These methods focus on rehabilitation and exercises for the brain which improve specific cognitive capacities. We present Cognitive Carnival, a computer game therapy based on cognitive exercises, designed to improve the child's motivation and engagement of the tasks. Three minigames were developed, each based on improving one of three cognitive prinicples: executive function, continuous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The therapists' rating of items [11][12][13][14][15][16], presented in Table III shows that the RGS was easy to use. RGS has functionalities and services that are clear and an interface that is simple, both of which contributed towards this rating.…”
Section: B Ease Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…The therapists' rating of items [11][12][13][14][15][16], presented in Table III shows that the RGS was easy to use. RGS has functionalities and services that are clear and an interface that is simple, both of which contributed towards this rating.…”
Section: B Ease Of Usementioning
confidence: 99%
“…One of the most crucial benefits of this game-based intervention is that even rural patients will get the chance to rehabilitate themselves, as the game systems could be distributed via the Internet [14]. In turn, the time for treatment and cost of human resource for each patient treated could be reduced, besides allowing home-bound patients to easily gain access to the treatments [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Achtman et al, found that games can help patients follow through with otherwise tedious therapy routines [1]. Games have been applied to teach sign language to deaf children [15], to support children with autism [11] and to provide cognitive training for children with Fetal Alcohol Syndrome [3].…”
Section: Games For Therapy and Rehabilitationmentioning
confidence: 99%
“…Serious games can be more engaging than paper exercises, accommodate built-in reward and motivation systems instead of real world incentives as the sole motivation for completing the rehabilitation tasks [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the most important advantage is the ability to distribute the game systems using the Internet. Therefore, they can easily reach remote areas [2]. Consequently, the human resource costs per patient treated and the treatment time decrease and home-bound patients can have easier access to the treatment [7].…”
Section: Introductionmentioning
confidence: 99%